2015
DOI: 10.1111/lam.12476
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of pentachloronitrobenzene by Arthrobacter nicotianae DH19

Abstract: The degradation of pentachloronitrobenzene (PCNB) by an individual bacterial strain is being reported for the first time. The efficient PCNB-degrading strain DH19 was isolated from ginseng rhizosphere soil and identified as Arthrobacter nicotianae. The strain could utilize PCNB as the sole carbon source for growth and degradation. In addition, strain DH19 could efficiently degrade dichlorodiphenyl trichloroethane, hexachlorocyclohexane, cypermethrin and cyhalothrin. Five metabolites from PCNB degradation were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Members of the genus Arthrobacter have been associated with the degradation of compounds, such as 4-chlorophenol ( 1 ), polychlorinated biphenyls ( 2 , 3 ), pentachloronitrobenzene, ( 4 ), 2-nitrobenzoate ( 5 ), atrazine ( 6 ), 2,4-dinitrotoluene ( 7 ), para -nitrophenol ( 8 ), 4-bromophenol ( 9 ), phenanthrene, and phthalates ( 10 , 11 ). Genome sequence data indicate that several strains of Arthrobacter are capable of degrading aromatic compounds, including Arthrobacter sp.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Members of the genus Arthrobacter have been associated with the degradation of compounds, such as 4-chlorophenol ( 1 ), polychlorinated biphenyls ( 2 , 3 ), pentachloronitrobenzene, ( 4 ), 2-nitrobenzoate ( 5 ), atrazine ( 6 ), 2,4-dinitrotoluene ( 7 ), para -nitrophenol ( 8 ), 4-bromophenol ( 9 ), phenanthrene, and phthalates ( 10 , 11 ). Genome sequence data indicate that several strains of Arthrobacter are capable of degrading aromatic compounds, including Arthrobacter sp.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Enterobacter hormaechei and Enterobacter coloacea show an interesting degrading capacity of the pharmaceutical effl uent (12). Similarly, several studies have reported the ability of the genus Pseudomonas and Arthrobacter for degrading the polluting compounds like sulfamethoxazole, chlorophenoxy acids, and pentachloronitrobenzene (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The lindane degradation also tested through kinetic studies as well. Wang et al (2015) isolated Arthrobacter nicotianae DH19 from Ginseng rhizospheric soil using morphological, biochemical tests, and 16S rRNA gene sequencing. This strain utilizes pentachloronitrobenzene (PCNB) as a sole carbon course for growth when it was inoculated in mineral salt medium.…”
Section: Resultsmentioning
confidence: 99%